Peningkatan Pembelajaran Mengenal Nilai Mata Uang dengan Menggunakan Model Pembelajaran Problem Based Learning bagi Siswa Tunagrahita - Sari, Winda; Nurhastuti, Nurhastuti; Agusta, Rini (Universitas Negeri Padang, 2023)
This research is motivated by the problems that researchers found at SLBN 1 Padang, namely mild mentally retarded children in class IX C in currency recognition activities, where children's learning outcomes are still very low in the concept of the nominal value of money, children do not know the nominal value of currency so that children experience difficulties in carrying out daily activities such as shopping in the canteen. For this reason, this study aims to improve the learning process of recognizing the value of the currency through a problem-based learning model and learning outcomes in recognizing currency values and their uses for mentally retarded children. The type of research used in this research is using classroom action research, this research uses two cycles, each cycle consisting of planning, action, observation, and reflection. Based on the results of this study, proves that the problem-based learning model can improve the learning process and learning outcomes in the ability to recognize currency values in mentally retarded children. This can be seen from the increased student learning outcomes in each cycle